Ferrocene and Pentaphosphaferrocene: A Comparative Study Regarding Redox Chemistry1. Issue 10 (31st January 2013) - Butovskiy, Mikhail V.; Balázs, Gábor; Bodensteiner, Michael; Peresypkina, Eugenia V.; Virovets, Alexander V.; Sutter, Jörg; Scheer, Manfred
<x xml:space="preserve">Abstract</x> Pentaphosphaferrocene redox chemistry: Unprecedented dianionic and PP coupled and monomeric products are obtained by the reduction of pentaphosphaferrocene with KH or K metal, whereas by oxidation a PP coupled P102+ ligand coordinated to two Cp*Fe units is obtained. The redox behavior clearly distinguishes pentaphosphaferrocene from its organometallic relative, ferrocene.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>